Thrombospondin 1 and Its Diverse Roles as a Regulator of Extracellular Matrix in Fibrotic Disease. (September 2019) - Murphy-Ullrich, Joanne E.
Thrombospondin 1 (TSP1) is a matricellular extracellular matrix protein that has diverse roles in regulating cellular processes important for the pathogenesis of fibrotic diseases. We will present evidence for the importance of TSP1 control of latent transforming growth factor beta activation in renal fibrosis with an emphasis on diabetic nephropathy. Other functions of TSP1 that affect renal fibrosis, including regulation of inflammation and capillary density, will be addressed. Emerging roles for TSP1 N-terminal domain regulation of collagen matrix assembly, direct effects of TSP1–collagen binding, and intracellular functions of TSP1 in mediating endoplasmic reticulum stress responses in extracellular matrix remodeling and fibrosis, which could potentially affect renal fibrogenesis, will also be discussed. Finally, we will address possible strategies for targeting TSP1 functions to treat fibrotic renal disease.